Literature Review: Faktor Risiko Obesitas Pada Remaja Di Indonesia - Bangkit Ary Pratama (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2023)
Obesity in adolescents that increase every year is a health problem that must be faced by all countries in the world, including Indonesia. Obesity can cause health problems in the future because obesity in adolescents will predict obesity as adults. Obesity is one of the main risk factors for chronic disease which can increase mortality. Addressing this problem at a critical population level will prevent the potential long-term impacts of adolescent obesity. The purpose of this literature review was to determine the risk factors for obesity adolescents in Indonesia. This research was a literature review research with data sources from international scientific journals published in PubMed with the theme of risk factors for obesity adolescents in Indonesia. The keywords used were